Community seed production and scaling of cereals, food legumes and potato innovations for mixed farming system of North Shoa, Ethiopia - Kassa, Yehuala; Ali, Bereket; Managido, Demis; Mamo, Dejenie; Girma, Natnael; Aynewa, Yetsedaw; Alem, Cherinet; Kemal, Seid Ahmed; Bishaw, Zewdie (International Center for Agricultural Research in the Dry Areas, 2023)
The highlands of North Shoa in Amhara region are dominated by cereals (wheat, barley and tef) followed by food legumes. The productivity of cereals and food legumes is low due to biotic and abiotic stresses as well as insufficient input supplies like certified seeds, planting materials, inoculants, and other inputs. Because of diseases and insect pests, acidity and water logging problems, farmers are reducing areas of food legumes and growing more cereals leading to low crop diversity that can reduce soil fertility and health, incomes, food diversity and increase disease threats. Several varieties of cereals, food legumes and potato were released by many agricultural research centers and did not reach farmers due to limited demonstration, lack of awareness and shortage of quality early generation seeds and planting materials. Poor access to quality seeds and planting materials contributes to low crop productivity and limited technology scaling in North Shoa. The scaling approach bundled crop technologies, agronomic innovations, and seed system innovations to accelerate the scaling and adoption.